Zanidatamab monotherapy or combined with chemotherapy in HER2-expressing gastroesophageal adenocarcinoma: a phase 1 trial - Funda Meric-Bernstam; Sun Young Rha; Erika Hamilton; Yoon-Koo Kang; Diana L. Hanna; Syma Iqbal; Keun-Wook Lee; Jeeyun Lee; Muralidhar Beeram; Do-Youn Oh; Jorge Chaves; Rachel A. Goodwin; et al. (Nature Communications)
Abstract There is a need for novel therapies for patients with previously treated HER2-positive gastroesophageal adenocarcinoma (GEA). This phase 1 (NCT02892123) dose-escalation and expansion trial evaluated zanidatamab (a dual HER2-targeted bispecific antibody) ± chemotherapy in previously treated patients with HER2-expressing, locally advanced/metastatic cancers. Here, we report the outcomes for GEA cohorts receiving zanidatamab monotherapy or with chemotherapy (paclitaxel or capecitabine). The primary endpoint was safety and tolerability. Secondary endpoints were objective response rate (ORR), disease control rate, progression-free survival, pharmacokinetics, and immunogenicity. Seventy patients were enrolled (n = 29 monotherapy; n = 41 combination therapy); most received prior HER2-targeted agents (monotherapy, 93%; combination therapy, 95%). With monotherapy, 69% of patients had any-grade treatment-related AEs (TRAEs); 17% had grade ≥ 3 TRAEs. The most common any-grade TRAEs were diarrhea (41%) and infusion-related reactions (24%). With combination therapy, 98% of patients had any-grade TRAEs; 51% had grade ≥ 3 TRAEs. The most common any-grade TRAEs were diarrhea (68%) and fatigue (44%). Confirmed ORR was 32.1% (95% confidence interval [CI] 15.9–52.4) with monotherapy and 48.6% (95% CI 31.9–65.6) with combination therapy. In heavily pre-treated patients with HER2-expressing GEA, zanidatamab ± chemotherapy had a manageable safety profile and promising antitumor activity.